2019
DOI: 10.5219/1237
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid profile after addition of humic acids and phytobiotics into diet of broiler chicken

Abstract: The aim of the study was analysed the effect of humic acids separately and humic acids in combination with phytobiotic as garlic and oregano powder on amino acid (AA) profile of the most valuable parts of Ross 308 chicken. A total of 200 pcs Ross 308 broiler chickens of mixed sex were randomly divided into 4 groups (n=50): control group (C) without supplementation, experiment group E1 (2% humic acids), E2 (80% humic acids and 20% garlic powder) and E3 (90% humic acids and 10% oregano powder). Fattening period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Interestingly, the current study demonstrated that dietary GA supplementation linearly reduces the contents of lysine in the breast and thigh muscles of laying hens. Although there is no information available to explain these results, a previous trial recorded that dietary humic acids decrease the level of lysine in the breast muscles of broiler chickens [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the current study demonstrated that dietary GA supplementation linearly reduces the contents of lysine in the breast and thigh muscles of laying hens. Although there is no information available to explain these results, a previous trial recorded that dietary humic acids decrease the level of lysine in the breast muscles of broiler chickens [ 40 ].…”
Section: Discussionmentioning
confidence: 99%